7-(9x+12)=1

Simple and best practice solution for 7-(9x+12)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-(9x+12)=1 equation:


Simplifying
7 + -1(9x + 12) = 1

Reorder the terms:
7 + -1(12 + 9x) = 1
7 + (12 * -1 + 9x * -1) = 1
7 + (-12 + -9x) = 1

Combine like terms: 7 + -12 = -5
-5 + -9x = 1

Solving
-5 + -9x = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -9x = 1 + 5

Combine like terms: -5 + 5 = 0
0 + -9x = 1 + 5
-9x = 1 + 5

Combine like terms: 1 + 5 = 6
-9x = 6

Divide each side by '-9'.
x = -0.6666666667

Simplifying
x = -0.6666666667

See similar equations:

| 3/5s=40 | | -10(x+1)+8=10 | | 4/7t=6 | | 13x+3=y | | 7x+14-2x=1+12-x-19 | | sin60=10/y | | 2/3=z=12 | | 5/8w=9 | | 1/6m=31 | | -29-7x=-3+3x-6 | | 2g=3g+8 | | a1=8;an=3/4(an-1) | | 54=7x-4 | | 4/0,02 | | 200p=400 | | 54=5x-8 | | y+3.19=12.95 | | 3.2s-5=5-1.85 | | 108=5x-8 | | 80=9x+13 | | g+7=2g | | -7x+13=19-x | | 7y+4ab=76 | | Y-3+2Y=9 | | 3x-1+5x+5=76 | | 2X=16-(X+9) | | -15=5(24+l) | | 2x+3=3x+-4 | | 4x=(2/-2y)/4 | | 6x+4=-4x-26 | | 1/2y-3=13 | | 85.00+7.50d=130.00 |

Equations solver categories